Enhancing E-Government Proactive Services Through Advanced Data Processing Technologies - Herrera, Jose (European Scientific Journal, ESJ, 2024)
The approach of citizens to the digital world allows the public sector to provide services that cross the frontiers of traditional citizen-administration relationships. Anticipating consumer needs, fostering more satisfying relationships, and reducing resolution times are some of the goals for a new era of electronic public sector services. A concise set of proactive systems is compiled to illustrate and analyse these options. This paper focuses on analysing the key role of Big Data and Digital Twin in public administrations as tools for providing Proactive Services (PAS). It is common for government administration to consider the use of disruptive technologies to enhance services designed to improve relationships with citizens. This paper explores the use of innovative technologies to increase the number of proactive services available within public administration (Proactive Public Services - PPS), the challenges they face, and the technical limitations that arise. A change in mindset is necessary. Paraphrasing an illustrious United States president in his inaugural address: â€œAsk not what citizens can do for administration â€“ ask what administration can do for its citizens.â€